2019
DOI: 10.5435/jaaos-d-16-00808
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Narcotic Use and Inferior Outcomes After Anatomic Total Shoulder Arthroplasty: A Clinical and Radiographic Analysis

Abstract: Chronic preoperative narcotic use seems to be a notable indicator of poor outcomes of anatomic total shoulder arthroplasty for glenohumeral osteoarthritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 24 publications
0
37
1
Order By: Relevance
“…Thompson et al 28 also found significant improvements in ROM for the opioid group (internal rotation, P ¼ .001; external rotation, P ¼ .004; forward flexion, P ¼ .001) and the nonopioid group (internal rotation, P ¼ .002; external rotation, P ¼ .001; forward flexion, P ¼ .001) from the preto postoperative period.…”
Section: Range Of Motionmentioning
confidence: 88%
See 4 more Smart Citations
“…Thompson et al 28 also found significant improvements in ROM for the opioid group (internal rotation, P ¼ .001; external rotation, P ¼ .004; forward flexion, P ¼ .001) and the nonopioid group (internal rotation, P ¼ .002; external rotation, P ¼ .001; forward flexion, P ¼ .001) from the preto postoperative period.…”
Section: Range Of Motionmentioning
confidence: 88%
“…Williams et al 32 and Morris et al 18 found significantly higher frequencies of back pain (P ¼ .007 and P ¼ .004, respectively) and depression (P < .04 and P ¼ .04) in the opioid group versus the nonopioid group. However, 3 of these studies 17,18,28 showed no statistically significant differences between groups in regard to age, sex, follow-up duration, smoking, diabetes, and heart disease.…”
Section: Patient Demographicsmentioning
confidence: 89%
See 3 more Smart Citations